Application of binary logistic regression analysis to factors that influence participation in the 2024 presidential election - Kurnia Ahadiyah; Ardiana Fatma Dewi; Shinta Hircatanu Romadewanti (Journal Focus Action of Research Mathematic (Factor M), 2024)
Social media plays a very influential role, especially in the world of politics and elections. The 2024 elections in Indonesia show how social media can influence political dynamics. This research aims to analyze the influence of social media on the political participation of IAIN Kediri students in the 2024 Presidential Election, as well as understand how social media shapes public opinion and polarizes political views, with a focus on its impact on political participation among students. Data from the Indonesian Internet Service Providers Association (APJII) shows that the majority of the Indonesian population actively uses social media, so political candidates use platforms such as YouTube, Facebook, Instagram, and TikTok to attract support. Social media accelerates the delivery of political messages and has the potential to strengthen polarization and spread misleading information. In this research, a binary logistic regression model is used to analyze the factors that influence student participation in the 2024 presidential election. The findings show that students who actively follow news in mass media have a 7,157 times greater chance of participating in the 2024 presidential election compared to those who do not follow the news. These results emphasize the importance of social media in motivating political participation among students and provide insight into how social media can be utilized to improve the integrity and quality of democracy.